Desenvolvimento de fibras compósitas ultrafinas de policaprolactona, pectina e zeólita faujasita para acondicionamento de cloxacilina - Rivas, Bárbara Bernardi Pedreira (2020)
Bovine mastitis and hoof diseases are infections responsible for great economic losses in the Brazilian agricultural sector. Such losses are associated with a reduction in milk and meat production leading to extreme cases of premature loss of infected animals. Conventional drug applications to treat these infections offer difficulties in application, causing pain and stress to the animal. In this sense, the use of fiber-based dressings is attractive because it is less invasive and provides better recovery conditions. Thus, the present study aimed to obtain biopolymeric fibers of polycaprolactone (PCL) and pectin (PEC) reinforced with faujasite zeolite (FAU) designed for cloxacillin loading. The FAU phase was optimized using the sol-gel method, with hydrothermal treatment varying between 2 and 6 h. Electrospinning parameters and polymers concentrations were varied in order to achieve PCL:PEC fibers with best properties. The optimal combination of the PCL: PEC blend was used to immobilize FAU (2.5% w/w) in order to improve ceramic reinforcement in the fibers. Finally, fibers bactericidal activity against Staphylococcus aureus were evaluated after loading 20% (w/w) cloxacillin. The X ray diffraction and infrared spectroscopy analyzes confirmed that 3 h of treatment formed the FAU phase without contamination, with polydispersed sizes in the range of 100 to 2000 nm and a high specific surface area of 347 m2 g-1. Zeta potential indicated that the particles are stable in dispersion, presenting a value of - 48 mV. Thus, FAU particles have high specific surface area and desirable dispersibility to reinforce the membrane with homogeneity. Scanning electron microscopy images showed that 10% (m/v) of PCL, flow of 1,2 mL h-1 and spinning distance of 10 cm yielded the most homogeneous fibers with the smallest diameter (240 nm). PCL:PEC thermogravimetric analysis profiles indicated that 10% (m/m) is the maximum pectin content capable of being inserted into the fiber. Fibers contact angle and microscopy images after degradation essay, in phosphate buffer medium (pH 5,5), showed that 10% PEC increased the membrane hydrophilicity, from 126° to 104°, accelerating the fiber degradation process. For PCL:PEC:FAU fibers it was possible to verify that the presence of FAU contributed to the increase in hydrophilicity, resulting in an angle of 81°, and also improved the material tensile strength, increasing from 0.5 to 3 MPa. The fibers loaded with cloxacillin presented an inhibition halo for the bactericidal assay with Staphylococcus aureus, indicating the antimicrobial activity through the diffusion of the antibiotic. In this way, PCL:PEC:FAU composite fibers presented desirable properties such as greater hydrophilicity, resistance to traction and bactericidal activity, suggesting its potential as transdermal membranes for wounds.